Tingkat Tutur pada Cerkak di Web Page Jawasastra (Sutasoma : Jurnal Sastra Jawa, 2023)
Javanese is one of the unique regional languages ​​because it has speech levels which are shown through spoken language in daily life conversations, while forms of written language are usually applied through Javanese literary works. This article aims to analyze the form and factors that cause the occurrence of speech levels used by the characters in cêrkak that represent people's lives. This study was studied using a qualitative descriptive method and analyzed using a sociolinguistic approach in the speech level study. The research data is sourced from documents of speech level that originating from dialogues between characters in five cêrkak on the Jawasastra web page. Research subjects were selected through purposive sampling, while data was collected through document analysis. The data were analyzed with an interactive analysis model through data collection, data reduction, data presentation, and drawing conclusions. In this study, four variations of speech levels were found, including: 12 data of ngoko lugu, 3 data of ngoko alus, 1 data of krama lugu, and 9 data of krama alus. The factors behind the use of each level of speech within the scope of Javanese society are due to differences in levels of education, economy, age, position, familiarity, and heredity.